The Dynamic Properties of Historic Timber-Framed Masonry Structures in Bursa, Turkey - M. Bilal Bağbancı; Özlem Köprülü Bağbancı (Shock and Vibration)
Timber-framed masonry structures are known as an effective earthquake load resisting system in high seismicity regions such as Bursa, Turkey. Intense earthquakes have occurred throughout history; however, many of the traditional timber structures have been able to survive without significant damage until the present day. In this study, six historic two-storied timber-framed masonry structures dating from the nineteenth century in Bursa City are investigated by using laboratory and in situ structural health monitoring tests. Although the houses have the same construction techniques, different masonry infill materials are used inside the timber frames. Stone, adobe, and brick are used as infill materials. Mud and lime mortars are used as binding materials. Mud mortar is used with stone and adobe materials. Lime mortar is used with brick material. The physical, mechanical, and dynamic parameters such as density, specific gravity, porosity, elastic modulus, frequencies, mode shapes, and damping ratios of the studied structures were investigated and the results were comparatively discussed. It is understood that the use of different infill materials affects the dynamic behaviors of these structures.